2022
DOI: 10.1097/md.0000000000031892
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of serum vitamin B12 and folate in patients with Crohn’s disease

Abstract: Crohn's disease is a chronic inflammatory condition that can involve any area in the gastrointestinal tract often involving the distal ileum where vitamin B12 is specifically absorbed. The aim of this study was to ascertain serum vitamin B12 and folate levels in order to investigate the correlation among these vitamin levels and disease activation, localization, duration and age at the onset of the disease.Study population included 103 patients with Crohn's disease and a healthy control group of 114 individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Similar serum B12 concentrations in CD and controls were reported by Geerling et al [47] and Yakut et al [61]. Geerling et al [45], Kallel et al [62], and Akbulut et al [63] reported significantly lower serum vitamin B12 concentrations in CD patients compared to HSs. Valentini et al [46] showed similar vitamin B12 deficiencies in CD patients in remission (9.6%) and HSs (0.0%) [30,43].…”
Section: Vitamin B12supporting
confidence: 76%
See 1 more Smart Citation
“…Similar serum B12 concentrations in CD and controls were reported by Geerling et al [47] and Yakut et al [61]. Geerling et al [45], Kallel et al [62], and Akbulut et al [63] reported significantly lower serum vitamin B12 concentrations in CD patients compared to HSs. Valentini et al [46] showed similar vitamin B12 deficiencies in CD patients in remission (9.6%) and HSs (0.0%) [30,43].…”
Section: Vitamin B12supporting
confidence: 76%
“…According to most authors, there is no difference in the plasma concentration of folic acid between IBD patients and HSs, but in numerous analyzed cases, folate supplementation is already used [21,45,47,61,62]. Contrary to the abovementioned studies, Akbulut et al [63], in a study including 103 CD patients and 103 healthy controls, reported a significantly lower serum concentration of folic acid in CD patients compared to HSs (p < 0.01). Yakut et al [61], in a study including 138 IBD patients (45 CD and 93 UC patients) and 53 HSs, noted a significantly higher rate of folate deficiency (28.8%) in CD patients (28.8%) compared to controls (3.7%) (p < 0.001).…”
Section: Folic Acidmentioning
confidence: 95%
“…Subsequent investigations should delve into the complex functions of supplementary blood-based indicators, such as folate and B12, concerning prediabetes-induced senescence [287]. It is crucial to investigate how dietary deficiencies, particularly regarding important nutrients like folate and B12, affect senescence and the effects of aging in prediabetic individuals [288].…”
Section: Potential Blood-based Biomarkers and Intervention Strategiesmentioning
confidence: 99%
“…These intervention strategies may improve the general health and longevity of prediabetic individuals while also delaying the onset of senescence. The Role of Additional Biomarkers (e.g., Folate and B12, Osteocalcin) in Future Research on Prediabetes-Induced Senescence [264] Subsequent investigations ought to delve into the complex functions of supplementary bloodbased indicators, like folate and B12, concerning prediabetes-induced senescence [268]. It is crucial to look into how dietary deficiencies, particularly in regard to important nutrients like folate and B12, affect senescence and the effects of aging on people who are prediabetic [269].…”
Section: Potential Blood-based Biomarkers and Intervention Strategiesmentioning
confidence: 99%